Shapeshifters: Black Girls and the Choreography of Citizenship. Issue 2 (1st June 2020) - Unknown
Abstract : Aimee Meredith Cox. 2015. Can Citizenship Care? Black Girls Reimagining Citizenship. Durham, NC, Duke University Press.